PERAN MEDIASI TRUST DAN SWITCHING COST PADA PENGARUH ANTARA SERVICE QUALITY DAN REPURCHASE LIKELIHOOD - Kadarusman, Kadarusman (Economic Faculty, Attahiriyah Islamic University, 2019)
The aim of this study is to examine the influence between service quality (SQ) and customer repurchase likelihood (CRL) is mediated by switching cost (SC) and trust (TR). Data were collected from 145 students of the Faculty of Economics in Malang City. SEM-PLS is used as an analytical tool to test the model. The results showed that SQ directly had a significant effect on CRL, TR, and SC. TR and SC have a significant effect on CRL. In addition, TR and SC have been proven to fully mediate SQ relations with CRL. The results of the study indicate that the relationship between SQ and CRL is a process model through TR and SC. Keywords: service quality, trust, switching cost, repurchase likelihood